2022
DOI: 10.52403/ijhsr.20220223
|View full text |Cite
|
Sign up to set email alerts
|

Self-Medication among Health Workers during the COVID-19 Pandemic in Southern Nigeria: Knowledge, Patterns, Practice and Associated Factors

Abstract: Background: The scare from the morbidity and mortality caused by the novel COVID-19 disease has continued with no specific cure in sight and many persons, including health care providers have resorted to self-medication. The study was intended to ascertain the prevalence of self-medication against COVID-19 among health workers in Rivers State. Methodology: A cross-sectional survey of health workers in Rivers State was carried out using self-administered questionnaires on self-medication against the COVID-19 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…The 62 included studies reported about the practice of on self-medication during COVID-19 in 29 different countries, of which 35 studies were from the Asian region namely Iran ( n = 5) ( 12 , 27 – 30 ), China ( 31 ), Indonesia ( n = 2) ( 32 , 33 ), Thailand ( 34 ), India ( n = 8) ( 11 , 35 – 41 ), Pakistan ( n = 5) ( 10 , 42 – 45 ), Turkey ( n = 3) ( 46 48 ), Bangladesh ( n = 5) ( 49 – 53 ), Saudi Arabia ( n = 3) ( 54 56 ), Jordan ( 57 ), Nepal ( 58 ); seven from Europe continent, Romania ( 59 ), Poland ( n = 2) ( 8 , 60 ), Netherlands ( n = 4) ( 61 64 ), Ireland ( 62 ), Norway ( n = 3) ( 62 64 ), Switzerland ( n = 2) ( 62 , 64 ), UK ( n = 2) ( 62 , 64 ), Sweden ( 63 ), Belgium ( 64 ); four from South America, Peru ( n = 3) ( 65 67 ), Colombia ( 68 ); three from North America, Mexico ( n = 3) ( 69 – 71 ); one from Oceania, Australia ( 72 ); and 12 from Africa, Kenya ( n = 2) ( 9 , 73 ), Togo ( n = 2) ( 74 , 75 ), Ethiopia ( 76 ), Nigeria ( n = 6) ( 77 82 ), and Sub-Saharan Africa ( 83 ).…”
Section: Resultsmentioning
confidence: 99%
“…The 62 included studies reported about the practice of on self-medication during COVID-19 in 29 different countries, of which 35 studies were from the Asian region namely Iran ( n = 5) ( 12 , 27 – 30 ), China ( 31 ), Indonesia ( n = 2) ( 32 , 33 ), Thailand ( 34 ), India ( n = 8) ( 11 , 35 – 41 ), Pakistan ( n = 5) ( 10 , 42 – 45 ), Turkey ( n = 3) ( 46 48 ), Bangladesh ( n = 5) ( 49 – 53 ), Saudi Arabia ( n = 3) ( 54 56 ), Jordan ( 57 ), Nepal ( 58 ); seven from Europe continent, Romania ( 59 ), Poland ( n = 2) ( 8 , 60 ), Netherlands ( n = 4) ( 61 64 ), Ireland ( 62 ), Norway ( n = 3) ( 62 64 ), Switzerland ( n = 2) ( 62 , 64 ), UK ( n = 2) ( 62 , 64 ), Sweden ( 63 ), Belgium ( 64 ); four from South America, Peru ( n = 3) ( 65 67 ), Colombia ( 68 ); three from North America, Mexico ( n = 3) ( 69 – 71 ); one from Oceania, Australia ( 72 ); and 12 from Africa, Kenya ( n = 2) ( 9 , 73 ), Togo ( n = 2) ( 74 , 75 ), Ethiopia ( 76 ), Nigeria ( n = 6) ( 77 82 ), and Sub-Saharan Africa ( 83 ).…”
Section: Resultsmentioning
confidence: 99%
“…Self-medication leads to resource waste, increased pathogens resistance, and antibiotic resistance ( 3 , 5 ). Also, self-medication is associated with incorrect dosage, incorrect route of administration, long-term use, improper storage, drug interactions, polypharmacy, and the risk of dependence and abuse, so it has become a serious public health problem worldwide ( 6 , 7 ). In most cases, the feeling of the mildness of the disease and no need to consult a doctor, previous pleasant experiences with self-treatment, the feeling of being able to self-care, and the lack of availability of a doctor increase self-treatment ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, socio-economic factors, lifestyle, sources of medical information, access to medicines, and the potential of managing some diseases through self-care are related to the continuous increase of self-treatment worldwide ( 7 , 8 ). On the other hand, self-treatment reduces the economic burden on patients, the high cost of hospital treatments, and the pressure on health care systems, limiting the number of hospital visits ( 6 , 9 ). Because self-treatment starts with self-diagnosis, the probability of its being incorrect is high, and even a correct diagnosis can be associated with the wrong treatment choice.…”
Section: Introductionmentioning
confidence: 99%
“…Self-medication has also been linked to incorrect dosage, poor administration techniques, prolonged use, improper storage, drug interactions, polypharmacy, and the possibility of dependence and addiction, making it a serious public health issue globally [ 8 ]. The risk of morbidity and death may increase as a result of resistance to readily accessible and reasonably priced antimicrobial medicines, thus limiting the already constrained therapeutic options in the management of prevalent infectious illnesses in developing countries [ 9 ].…”
Section: Introductionmentioning
confidence: 99%